Recent advances in two‐dimensional materials for hydrovoltaic energy technology. Issue 2 (28th January 2023) - Liu, Zhihang; Liu, Chao; Chen, Zhaotian; Huang, Honglan; Liu, Yifan; Xue, Liang; Sun, Jingwen; Wang, Xin; Xiong, Pan; Zhu, Junwu
Abstract: Hydrovoltaic energy technology that generates electricity directly from the interaction of materials with water has been regarded as a promising renewable energy harvesting method. With the advantages of high specific surface area, good conductivity, and easily tunable porous nanochannels, two‐dimensional (2D) nanomaterials have promising potential in high‐performance hydrovoltaic electricity generation applications. Herein, this review summarizes the most recent advances of 2D materials for hydrovoltaic electricity generation, including carbon nanosheets, layered double hydroxide (LDH), and layered transition metal oxides and sulfides. Some strategies were introduced to improve the energy conversion efficiency and the output power of hydrovoltaic electricity generation devices based on 2D materials. The applications of these devices in self‐powered electronics, sensors, and low‐consumption devices are also discussed. Finally, the challenges and perspectives on this emerging technology are outlined. Abstract : Hydrovoltaic energy technology that generates electricity directly from the interaction of materials with water has been regarded as a promising renewable energy harvesting method. This review summarizes the most recent advances of 2D materials for hydrovoltaic electricity generation, including carbon nanosheets, layered double hydroxide, and layered transition metal oxides and sulfides. Perspectives toward the future applications of 2D materials in hydrovoltaic electricity generation are also outlined.